You can even take the three consecutive numbers as

As per the question, `(x-1) + x + (x+1) = 93`

`x-1+x+x+1 = 93`

Now solve for `x`

`3x = 93`

`x = 93/3`

`x = 31`

`therefore ` the required numbers are `31-1, 31, 31+1 ` i.e, `30,31 and 32`

To solve this, assume that the three consecutive numbers are all integers. Then, assign a variable that represents the first integer. Let it be x. So the next two integers are x+1 and x+2.

Then, add these three integers and set it equal to the given sum.

`x + (x+1)+(x+2)=93`

And solve for x.

`3x+3=93`

`3x=93-3`

`3x=90`

`x=90/3`

`x=30`

This is the first integer. The other two integers are:

second integer `= x + 1 = 30+1 = 31`

third integer `= x+2=30+2=32`

**Therefore, the three consecutive numbers that add up to 93 are 30, 31 and 32.**